THE PHANTOM OF THE SUBWAY - Stilton, Geronimo; Tabasco, Blasco; Codana, Guy (New York : Scholastic Inc., 2004)
When he hears reports of a ghost haunting New Mouse City s subway tunnels, Geronimo sets out to investigate the story
"Original title: Il fantasma del metro"--T.p. verso
Keywords: Animals -- Juvenile fiction; Mice -- Fiction; Detective and mystery stories, English